2007
DOI: 10.1007/s00011-006-6111-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in upper airways inflammatory diseases

Abstract: In the human respiratory tract, the main production sites of exhaled nitric oxide (NO) are the nose and paranasal sinuses. In the upper airways, NO has been suggested to be involved at different levels with regulatory, protective, defensive or deleterious effects. Therefore, we review some aspects of the origin, metabolism, and functions of NO in the upper airways, together with the role of NO in some upper airways inflammatory diseases. Furthermore, we discuss the recent improvements in nasal NO measurements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 116 publications
6
120
2
Order By: Relevance
“…NO is a free radical gas molecule that intervenes in a large number of fundamental cellular processes such as vascular regulation, neurotransmission, and immunity (3,4). NO reacts in water with oxygen and its reactive intermediates to yield (i) stable anions such as NO 2 Ϫ and NO 3 Ϫ , (ii) unstable higher oxides such as N 2 O 3 , and (iii) unstable peroxides (ONOO Ϫ ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO is a free radical gas molecule that intervenes in a large number of fundamental cellular processes such as vascular regulation, neurotransmission, and immunity (3,4). NO reacts in water with oxygen and its reactive intermediates to yield (i) stable anions such as NO 2 Ϫ and NO 3 Ϫ , (ii) unstable higher oxides such as N 2 O 3 , and (iii) unstable peroxides (ONOO Ϫ ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in maturing DC, protein degradation by caspases was inhibited, presumably by NO (1). NO is a central messenger molecule in vascular regulation, immunity, and neurotransmission (3,4). Despite the fact that NO was produced in large amounts in lipopolysaccharide (LPS)-treated DC, it is still unclear whether NO alone can contribute directly to the initiation and induction of DC maturation and T cell proliferation, respectively, in the absence of LPS.…”
Section: Dendritic Cells (Dc)mentioning
confidence: 99%
“…To date, nNO has been reported to be very low, almost exclusively among subjects with PCD, and to separate convincingly between the presence and absence of PCD [3][4][5][6][7][8]. However, overlap in nNO values have been reported between PCD and other pulmonary diseases with symptoms mimicking PCD [9][10][11]. Hence, the true discriminative power of nNO in less selected, mixed population of patients referred for diagnostic testing of PCD will need to be settled before the role of nNO in the diagnosis of PCD can be fully appreciated.…”
mentioning
confidence: 99%
“…In 1998, Robert F. Furchgott, Ferid Murad and Louis J. Ignarro were awarded the Nobel Prize in Physiology or Medicine for their discoveries concerning NO as a signaling molecule in the cardiovascular system. Since 1991, when Gustafsson et al [5] discovered that NO is present in exhaled breath of humans – and 2 years later, when Alving et al [6] showed that exhaled NO is increased in patients with asthma – several aspects of exhaled and nasal NO have been studied [19]. Actually, the molecule NO was named ‘molecule of the year’ in 1992 by the journal Science .…”
Section: Introductionmentioning
confidence: 99%